Proton dynamics in molecular solvent clusters as an indicator for hydrogen bond network strength in confined geometries. Issue 6 (30th January 2020) - Saak, Clara-Magdalena; Richter, Clemens; Unger, Isaak; Mucke, Melanie; Nicolas, Christophe; Hergenhahn, Uwe; Caleman, Carl; Huttula, Marko; Patanen, Minna; Björneholm, Olle
Abstract : The size-dependence of proton-dynamics occurring upon core-ionisation is linked to a weakening of the hydrogen-bond network in molecular clusters. Abstract : Hydrogen bonding leads to the formation of strong, extended intermolecular networks in molecular liquids such as water. However, it is less well-known how robust the network is to environments in which surface formation or confinement effects become prominent, such as in clusters or droplets. Such systems provide a useful way to probe the robustness of the network, since the degree of confinement can be tuned by altering the cluster size, changing both the surface-to-volume ratio and the radius of curvature. To explore the formation of hydrogen bond networks in confined geometries, here we present O 1s Auger spectra of small and large clusters of water, methanol, and dimethyl ether, as well as their deuterated equivalents. The Auger spectra of the clusters and the corresponding macroscopic liquids are compared and evaluated for an isotope effect, which is due to proton dynamics within the lifetime of the core hole (proton-transfer-mediated charge-separation, PTM-CS), and can be linked to the formation of a hydrogen bond network in the system. An isotope effect is observed in water and methanol but not for dimethyl ether, which cannot donate a hydrogen bond at its oxygen site. The isotope effect, and therefore the strength of the hydrogen bond network, is more pronounced in water than in methanol. Its value depends on the average size of the cluster, indicating that confinement effects change proton dynamics in the core ionised excited state.